2013
DOI: 10.1002/eji.201343690
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive transfer of cytomegalovirus‐specific effector CD4+T cells provides antiviral protection from murine CMV infection

Abstract: Cytomegalovirus (CMV) infects a majority of the human population and establishes a lifelong persistence. CMV infection is usually asymptomatic but the virus carries pathogenic potential and causes severe disease in immunocompromised individuals. T-cell-mediated immunity plays an essential role in control of CMV infection and adoptive transfer of CMVspecific CD8 + T cells restores viral immunity in immunosuppressed patients but a role for CD4 + T cells remains elusive. Here, we analyzed in adoptive transfer stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 43 publications
3
35
0
Order By: Relevance
“…In mice, CD4 T cells are absolutely required to control mouse cytomegalovirus (MCMV) replication in the salivary glands-the key site of viral dissemination, where CD8 T cells can exert no control (14,15)-and also contribute to immune control in several other organs. Adoptive transfer of MCMV-specific transgenic CD4 T cells provides some protection in immunocompromised mice (16), and cotransferring CMV-specific CD4 T cells reduces viral load and promotes "help" for CMV-specific CD8 T cell responses in patients receiving cellular immunotherapy (17).…”
mentioning
confidence: 99%
“…In mice, CD4 T cells are absolutely required to control mouse cytomegalovirus (MCMV) replication in the salivary glands-the key site of viral dissemination, where CD8 T cells can exert no control (14,15)-and also contribute to immune control in several other organs. Adoptive transfer of MCMV-specific transgenic CD4 T cells provides some protection in immunocompromised mice (16), and cotransferring CMV-specific CD4 T cells reduces viral load and promotes "help" for CMV-specific CD8 T cell responses in patients receiving cellular immunotherapy (17).…”
mentioning
confidence: 99%
“…Walton et al revealed that the mechanism of CD4 T cell immune control in the salivary glands of MCMV infected mice was via direct secretion of IFN-γ, which induced antiviral signaling on non-hematopoietic cells (134). Adoptive transfer experiments of MCMV-specific effector CD4 T cells to immune-compromised mice was found to be protective during pathogenic MCMV infection and IFN-γ was a vital mediator of this protective capacity (135). Despite the apparent importance of CD4 T cells in viral control in the above studies, there was no specific link to CD4 CTL.…”
Section: Infections In Which Cd4 Ctl Are Protectivementioning
confidence: 99%
“…While the humoral and innate responses are essential for the early response to infection [1, 3, 4], cellular immunity is required to control latency and prevent CMV reactivation in latently infected individuals [1]. CD8 + cytotoxic T cells (CTL) and CD4 + T helper (Th) cells are both required to assure efficient immune protection against CMV reactivation [1, 58]. Primary infection is dominated by CD8 + T cell response, preferentially targeting CMV immediate early-1 (IE-1) antigen, while long-term recovery is dominated by CD4 + T cell response and a switch of reactivity toward CMV lower matrix phosphoprotein 65 (pp65) [6, 811].…”
Section: Introductionmentioning
confidence: 99%